A Review Article – on Jeevaniya Mahakashaya - Khandelwal, Priyanka; Sivan, Archana; Singh, Chandan; Purvia, Rajendra Prasad; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2022)
Jeevaniya Mahakashaya are a group of 10 Drugs, that have many ways to work, including working on the immune system directly, by turning down some proteins and turning up others. These dravya’s are very much conducive for health. In our Ayurvedic classics the knowledge about Mahakashaya were dealt in Charaka Sutra Sthana 4th chapter, according to karma. Acharya has mentioned about 50 Mahakashayas, each having about 10 drugs. In this, the first and the foremost Mahakashaya is Jeevaniya Mahakashaya. They are a group of drugs which are beneficial for life. Most of the drugs present in this group are very essential for the whole functioning of the body in terms of providing energy and sustaining life activites. This can be compared to various nutrients and immunity boosters.